Performance Management pada YPAC Jakarta - Eriesko Kusuma Wisudhana; Dwi Idawati (Research Center and Case Clearing House PPM School of Management, 2021)
The purpose of this study is to develop a performance management design at Yayasan Pembinaan Anak Cacat Jakarta. The performance management design is utilised as a strategic step in managing the performance of the employees at YPAC Jakarta. The study is categorized as qualitative and quantitative descriptive method. Using the theoretical approach to business strategy and Human Resources Management (HRM) strategy from Miles and Snow (1984). Moreover, the performance management theory proposed by Armstrong (1994) and Aguinis (2013) is observed as well. To measure the performance, Mixed model Theory by Spencer and Spencers (1993) is put into account. The data collection method used is using interviews with the sources; Management Board, Managing Director and General Manager. Another method of data collection is to use a survey using a questionnaire which distributed to 72 respondents to obtain employees perception in regard to the implementation of performance management at YPAC Jakarta. The list of questions in the questionnaire is adopted and necessarily modified from the previous study which was developed by Weiss and Hartle (1997). The result of this study shows that the performance management that must be improved is at the stage of the performance appraisal as well as of the performance review, which each has below- average values of 3,12 out of 3,2. However, the results of the planning and execution stages of performance actually shows that there are several aspects that are still lacking. Based on the identified problems in the performance management implementation, therefore the improvement plan is drafted.